DETERRING AND THREATENING IN THE RUSSIAN-UKRAINIAN WAR: A GAME THEORY PERSPECTIVE - Adelina Andrei (Economy and Sociology)
Russia’s full-scale invasion of Ukraine in 2022 marked a significant turning point in the post-World War II history of Europe, with the realist and idealist views on international relations offering contrasting interpretations of its underlying sources. While each perspective provides valuable insights, neither captures entirely the complex dynamics of foreign affairs, which frequently straddle a middle ground between the conflictual and cooperative states of nations. This paper takes on a game theory approach to bridge the gap between the realist and idealist views on international relations, with the analysis of two scenarios: a limited deterrence game, viewing the conflict as a proxy war between NATO and Russia, and an extended deterrence game, seeing the conflict as a direct war between Russia and Ukraine with potential help from NATO. The findings offer a nuanced understanding of the dynamics between Russia, Ukraine, and NATO with practical significance, suggesting that NATO should have employed a strategy of decisive support for Ukraine, as anything less allowed Russia to underestimate the consequences of the full-scale invasion.